HPB P21 Surgery for peri-hilar cholangiocarcinoma: The Liverpool hepatobiliary unit experience. (7th December 2022) - Gilbert, Timothy; Bird, Nicholas; Quinn, Marc; Diaz-Nieto, Rafael; Jones, Robert; Fenwick, Stephen; Malik, Hassan
Abstract: Background: Surgery for perihilar cholangiocarcinoma (pCCA) offers the only possibility of long-term survival but remains a formidable undertaking associated with significant post-operative morbidity and mortality. We aim to share our experience of managing these complex patients within a high-volume UK centre. Methods: A retrospective review of a prospectively maintained database was performed on all patients who underwent resection for pCCA at our unit between 2009–2021. Kaplan–Meier analysis was used to estimate overall and disease-free survival (OS/DFS). Post-op complications were graded using the Clavien-dindo classification and reported as minor (Grade1/2) or major complications (Grade3/4). Results: 102 patients underwent surgery for pCCA at our unit between 2009–2021. The majority of patients required pre-operative biliary drainage via ERCP and metal stent insertion. Following MDT and CPEX assessment eligible patients underwent an initial staging laparoscopy followed by curative resection. 30% of patients required a PVE to increase the proposed functional liver remnant volume prior to surgery. The majority of patients (76%) had Bismuth-Corlette IIIA/B or IV disease necessitating a major liver resection along with radical bile-duct resection. Post-op morbidity rates were high with 42% experiencing a major (grade3/4) complication. Of these patients 14 individuals subsequently died culminating in a 90-day mortality rate of 13.7%. Median LOS was 11 days (IQR 5–59). Median OS for the entire cohort was 36.3 months (CI:26.7–45.8) with a nominal 5-year survival rate of 34.6%. 40% of patients received adjuvant chemotherapy post-op. During follow up 59% of patients suffered disease recurrence with a median DFS of 20.1 months (CI: 11.5–33.5). The administration of palliative chemotherapy upon recurrence was associated with an improvement in survival of 11 vs 5.3 months (HR 3.5 p 0.01). Conclusions: Surgery for pCCA remains a significant undertaking for both patient and clinician with high rates of morbidity and mortality. Long term survival is achievable but recurrence rates remain a challenge. Overall our mortality, morbidity and survival rates are comparable to that reported in other Western centres.